THE ROLE OF BANK GUARANTY IN CONSTRUCTION CONTRACTS BETWEEN THE GOVERNMENT AND CONTRACTORS - Mulada, Diman Ade (Jurnal IUS (Kajian Hukum dan Keadilan), 2013)
In government project, to guarantee the assignor (government) to acquire the  project finished on the time and quality promised by the contractor, it required a guarantee  of the contractor for the government as mentioned in Article no 67 paragraph (1) of Presidential Decree No. 54 of 2010 concerning the Procurement of Goods / Services.  One of the guarantees often used by contractors is  a guarantee bank. In the implementation of a  contract between the government and contractors who use the guarantee bank, they must go through some steps.. First stage is the preparation for the selection of the construction work, and the second stage is to carry out the selection of construction work, in which the contractor must submit a tender guarantee of bank guarantee.  The third stage is the signing of the contract, in which the contractor must submit a bank guarantee of warranty execution and the fourth stage is the execution of contracts where the contractor must submit a bank guarantee of an advance money if the contractor will take an advance money and submit a bank guarantee of a maintenance warranties when the contractor has completed the work.  When a default happened by either party, the solution is as follows.  If related  to the contracts, the problem is solved through a discussion, and then if no way out, the problem may be solved through arbitration or courts. In relation to the bank guarantee, if a default happened by the contractor,  the solution is by deliberation between the bank and the contractor in  order that the contractor complete the arrears, however, if the contractor has no intention to complete the arrears, the bank  may issue a maximum of three (3) warning letters. Moreover, if the bank has issued three warning letter sand the contractor still does not respond, then the bank will make disbursements against opponents guarantees that have been submitted by the contractor.Keywords: Bank Guarantee, Contraction Contract.